THE AESTHETIC VALUE AND THE EFFECT OF COMMUNICATIVE IN THE ANTHOLOGY POEMS TIDAK ADA NEW YORK HARI INI BY M. AAN MANSYUR (NILAI ESTETIKA DAN EFEK KOMUNIKATIF DALAM ANTOLOGI PUISI TIDAK ADA NEW YORK HARI INI KARYA M. AAN MANSYUR) - Ali Mubarok, Azys; Rasyid, Yumna; Lustyantie, Ninuk (Jurnal Gramatika, 2018)
The objective of this research was to examine the reaction of readers to the aesthetic value and the effect of communicative contained in the anthology poems Tidak Ada New York Hari Ini the work of M. Aan Mansyur based on the study of the reception of the reader. The aesthetic value and the effect of communicative examined based on the theory of Jauss about the ‘Horizon of Expectations’ that is, the interaction between readers and literary works. This research was a qualitative study using interviews and focus group discussion (FGD) to the students of the University of Sultan Ageng Tirtayasa Banten dan content analysis. The results showed that in the anthology of poetry Tidak Ada New York Hari Ini, poets present aesthetic value through the use of hyperbole, personification, metaphor, irony, and repetition of language so that poetry becomes beautiful. Then, the communicative effect obtained by the reader in the form of entertainment effects, beauty, motivation, and life lessons.Keywords: aesthetic value, communicative effect, anthology of poetry, reader receptions